Identification of Trends in Business Promotion and Marketing Using Video-Based Content on Social Media - Juanna, Andi; Monoarfa, Mohamad Agus Salim; Podungge, Robiyati; Tantawi, Rezkiawan (Jambura Science of Management, 2024)
Purpose: There are many ways to promote a business in the technology era. One of them is promotion and marketing using video content based on social media. Many studies have reported the importance of social media in supporting business marketing. However, few have studied the effectiveness of video content on social media to become increasingly modern applications in recent years. For this reason, we have identified what trends have inspired business people to promote their businesses using videos through social media content.Design/Methodology/Approach: This research uses a qualitative method with a literature study approach. After collecting the data and analyzing it involving the data coding system, the core of the data, and concluding, the point is to get answers that answer the problems and enlarged studies with high validity.Findings: This study concluded that social media applications, especially videos, have become a very advanced trend to drive business, especially marketing and promotion because video applications are easy to prepare and attractive to the audience. Thus these results become reference material for further studies.